STUDY OF THE IMMUNOTROPIC ACTIVITY OF THE SUPRAMOLECULAR COMPLEX OF FENBENDAZOLE - A. I. Varlamova; K. G. Kurochkina; N. V. Danilevskaya (Российский паразитологический журнал)
The purpose of the research is to study the immunotoxic properties of the supramolecular complex of fenbendazole (CMF).Materials and methods. The study of the immunotoxic properties of SMF was performed using the agglutination reaction and delayed-type hypersensitivity. In each experimental group, there were 7–8 CBA × C57BL / 6 mice weighing 16–18 g. The CMF was administered once intragastrically at a therapeutic dose of 20 mg/kg for the active substance, in a tenfold dose – 200 mg/kg, the basic drug – fenbendazol asked in a tenfold dose of 20 mg/kg. Control groups of animals received starch paste. Then the mice were immunized intraperitoneally with a 3 % suspension of sheep erythrocytes (test antigen) and distributed into 8 groups. The effect of drugs on antibody production was determined in the hemagglutination reaction, the antibody titer in the serum in the microvariant of the direct hemagglutination reaction with the calculation of the reaction index. The effect of the drug on cellular immunity was established in a delayed-type hypersensitivity reaction (DTH) to sheep erythrocytes.Results and discussion. The introduction of the tested drugs had no inhibitory effect on antibody production in mice of the experimental groups: 6.5±0.22; 6.17±0.47 and 7.75±0.25 (log2) compared with the control – 7.67±0.21 (log2). Reaction indices were respectively 0.85; 0,80 and 1,01. Oral administration of a single CMF in therapeutic (20 mg/kg) and in a tenfold therapeutic dose (200 mg/kg) did not affect the cellular level of immunity. The shifts in the inflammatory response index in animals were 9.05±3.47 and 10.05±2.25% respectively. The introduction of the basic drug stimulated the reaction of HRT, which was manifested by an increase in the inflammation index (21.06±3.32%) compared with the control group (9.27±3.91%).